Salmonella enterica employs metabolic adaptation to plant environments - Han, Min; Duan, Yongming; Schikora, Adam (Frontiers in Plant Science, 2025)
Plant environments are considered reservoirs for Salmonella enterica. While exploring Salmonella’s adaptation mechanisms to plant environments, metabolic regulation has frequently gained attention. However, these findings have never been summarized or discussed. This review focuses therefore, on the metabolic adaptations employed by S. enterica to adapt to plant environments, including nutrient availability, acquisition, and its pathway regulation. Plant environments provide diverse carbon sources (e.g. sugars, organic acids, glycerol, and fatty acids) and amino acids, while S. enterica dynamically reprograms its metabolism to prioritize glucose via glycolysis, activate gluconeogenesis under sugar limitation, and utilize alternative carbon sources including glycerol or fatty acids. Amino acid biosynthesis, notably cysteine, also seemed critical in S. enterica adaptation to plant environments. These adaptive mechanisms highlight how S. enterica balances biosynthesis and catabolism of diverse nutrients in plant environments, offering insights into its metabolic plasticity as an adaptive strategy in agricultural ecosystems.